UPAYA PENGEMBANGAN KURIKULUM KOLABORASI DI MIS NURUL FALAH MUNCUL - Wildan Alfauzi; Hanzela Alaras; Day Ismail; Mega Utami; Siti Salsabila; Hendrayadi Hendrayadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe and analyze collaborative curriculum development efforts at MIS Nurul Falah Muncul, South Tangerang, in the context of strengthening 21st-century skills and implementing curriculum policies for elementary madrasas. The study employed a descriptive qualitative approach, with data collection techniques including interviews, observations, and documentation studies of curriculum documents and learning materials. Data analysis was conducted through interactive data reduction, display, and conclusion drawing. The results indicate that collaborative curriculum development at MIS Nurul Falah Muncul is directed at: (1) formulating the madrasa's vision, mission, and objectives, emphasizing strengthening Islamic character, collaboration skills, and basic literacy; (2) integrating Islamic values ​​and 21st-century skills into the curriculum structure and lesson plans; and (3) developing cooperative learning models and cross-subject collaborative projects, particularly in Islamic Religious Education and general themes. These efforts are supported by the formation of a curriculum development team, teacher training, and collaboration with parents and the madrasa committee.